Nonlinear Absorption and Refraction of Picosecond and Femtosecond Pulses in HgTe Quantum Dot Films - Arturs Bundulis; Ivan A. Shuklov; Vyacheslav V. Kim; Alaa A. Mardini; Jurgis Grube; Janis Alnis; Anna A. Lizunova; Vladimir F. Razumov; Rashid A. Ganeev (Nanomaterials, 2021)
We report measurements of the saturated intensities, saturable absorption, and nonlinear refraction in 70-nm thick films containing 4 nm HgTe quantum dots. We demonstrate strong nonlinear refraction and saturable absorption in the thin films using tunable picosecond and femtosecond pulses. Studies were carried out using tunable laser pulses in the range of 400–1100 nm. A significant variation of the nonlinear refraction along this spectral range was demonstrated. The maximal values of the nonlinear absorption coefficients and nonlinear refractive indices determined within the studied wavelength range were −2.4 × 10−5 cm2 W−1 (in the case of 28 ps, 700 nm probe pulses) and −3 × 10−9 cm2 W−1 (in the case of 28 ps, 400 nm probe pulses), respectively. Our studies show that HgTe quantum dots can be used in different fields e.g., as efficient emitters of high-order harmonics of ultrashort laser pulses or as laser mode-lockers.